Intellectual capital disclosures: before and after issuance of management commentary / Khadijah Suria - Suria, Khadijah (2013)
This study seeks to investigate the trends of Intellectual Capital Disclosures (ICD) by Malaysian companies before and after the issuance of the Practice Statement on Management Commentary in December 2010. The voluntary disclosures of 30 listed companies were reviewed and a total of 120 annual reports were examined from year 2009 to 2012. The study employed a content analysis method with a checklist of 24 IC attributes, of which, 9 are from internal capital, 9 from external capital and 6 from humancapital. This study employs a scoring scale from ‘1’ to ‘5’to distinguish the level of ICD. In addition, this study also analyzed the relationship between ICD and firm characteristics, namely company size, leverage, profitability and growth. The theories underpinning the conceptual framework are agency theory, stakeholder theory and signaling theory. The study used inferential statistics to examine the relationship between firm characteristics and ICD. The findings showed there are significant increasing trends of ICD after the issuance of Management Commentary in 2010. The study also found that none of the firm characteristics were associated to the disclosure of IC. Among the three IC components, external capital was the most disclosed as compared to internal and human capital. This study would be interesting to give insight to the standard setters on the readiness of Malaysian companies in reporting their IC.